2020
DOI: 10.30996/dih.v16i2.3439
|View full text |Cite
|
Sign up to set email alerts
|

Implikasi Kebijakan Dan Diskriminasi Pelarangan Ekspor Dan Impor Minyak Kelapa Sawit Dan Bijih Nikel Terhadap Perekonomian Indonesia

Abstract: The creation of free trade provides a large advantage and role in driving the economic growth of a country, especially for developing countries that have abundant natural resources. One of the systems in free trade carried out by countries in the world in buying and selling produce is known as an export-import system. Where the seller is usually referred to as an exporter and the buyer is referred to as an importer. Like the general trading system, in international trade there are also obstacles that can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
1
4
0
9
Order By: Relevance
“…Based on the t value (6.56>1.97), it can be concluded that there is a positive relationship between the number of European palm oil imports and Indonesian palm oil exports. This is in line with many theories which say that the European market is one of the markets that plays an active role in increasing the number of Indonesian palm oil exports (Rahayu and Sugianto 2020). According to Oosterveer (2020) the role of Europe in palm oil policy is a determinant of world palm oil demand which directly affects the performance of Indonesian palm oil exports.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Based on the t value (6.56>1.97), it can be concluded that there is a positive relationship between the number of European palm oil imports and Indonesian palm oil exports. This is in line with many theories which say that the European market is one of the markets that plays an active role in increasing the number of Indonesian palm oil exports (Rahayu and Sugianto 2020). According to Oosterveer (2020) the role of Europe in palm oil policy is a determinant of world palm oil demand which directly affects the performance of Indonesian palm oil exports.…”
Section: Resultssupporting
confidence: 79%
“…Palm oil has become a significant commodity in the last two decades. This commodity is the most consumed vegetable oil globally (Alii, Karimi, and Febriamansyah 2021;Rahayu and Sugianto 2020;Tyson and Meganingtyas 2020). Palm oil has many derivative products that are quickly processed into various household needs (Oosterveer 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Solving problems through deductive analysis applies a law in abstracto to solve legal problems in concrete. 22 Analysis using this deductive method begins with a general discussion to a specific discussion or a more in-depth discussion that will be discussed and has the aim of finding conclusions.…”
Section: Analysis Of Legal Materialsmentioning
confidence: 99%
“…Hal ini mengakibatkan Uni Eropa mengajukan gugatan untuk Indonesia kepada World Trade Organization (WTO). Gugatan tersebut dikarenakan selama ini Uni Eropa sangat bergantung dengan ekspor bijih nikel Indonesia, yang digunakan untuk seluruh pembangunan, teknologi, dan juga otomotif (Rahayu & Sugianto, 2020). Kebijakan larangan ekspor CPO juga menyebabkan banyak permasalahan seperti over supply pasokan CPO yang mengakibatkan harga Tandan Buah Segar (TBS) sawit di Indonesia turun drastis (Mahendra & Sulaeman, 2023).…”
Section: Tabel 4 Hasil Uji One Sample T-testunclassified